Pt-support interaction and nanoparticle size effect in Pt/CeO2–TiO2 catalysts for low temperature VOCs removal. (February 2021) - Shi, Yijun; Wang, Jialu; Zhou, Renxian
Abstract: A series of Pt/CeO2 –TiO2 catalysts (0.5 wt% Pt) with size-controllable Pt nanoparticles were prepared by a modified ethylene glycol reduction method and the Pt particle size effect of Pt/CeO2 –TiO2 catalysts on benzene and 1, 2-dichloroethane (DCE) degradation was investigated. It reveals that the metal-support interaction of PtOx species and CeO2 –TiO2 mixed oxides is enhanced by the reduced Pt particle sizes. The formation of more Pt 2+ species and stronger redox properties at low-temperature resulted by the enhanced metal-support interaction of Pt/CeO2 –TiO2 catalysts both greatly promotes the deep oxidation for benzene and C2 H3 Cl byproduct during DCE degradation at low temperature. Pt/CeTi-11 with the smallest average Pt particle size (1.53 nm) exhibits the highest activity among all the catalysts for benzene degradation, with T90% of only 152 °C (1000 ppm, GHSV = 15, 000 h −1 ). However, more acidic sites (especially the strong acid) were formed on the Pt/CeO2 –TiO2 catalysts with bigger Pt nanoparticle (>2.95 nm), contributing to activate and convert DCE to C2 H3 Cl. More importantly, Pt/CeO2 –TiO2 catalysts are extremely stable in DCE degradation reaction, and have been scarcely influenced by the presence of benzene and water in the feed gases. Graphical abstract: Image 1 Highlights: Stronger PM-Ce interaction results in more Pt 2+ species and better redox properties. Smaller Pt nanoparticles (<2.45 nm) promote the deep oxidation of VOCs. Bigger Pt nanoparticles (>2.95 nm) are helpful for the activation of DCE. Pt/CeO2 –TiO2 catalysts show very stable activities for DCE degradation.